e-CarRental : mobile application system for booking car rental / Syahidatul Husna Isa - Syahidatul Husna, Isa (2016)
Currently, booking car rental process around Tapah is using manual process. There were several problems occurs on customer which is customer have to find contact number’s owner of the car rental from other people and call the owner for booking. Customer has to ask many questions before they want to booking car such as how many cars is available, price of the car for an hour or half day, and many more. When the calling session finish, customer has to fill the booking form that the owner give before customer can rent that car. Customer has to do many works for booking car. The problems occurs because lack of advertisement for car rental and no efficient system or application that the owner use. The solution has been come out on solving these various problems that always occurs on customer. So, this project will be implemented in mobile application system. A mobile application is an application that is accessed through mobile phone or smart phone. Therefore with this mobile application method hopefully will help customer and also the owner of the car rental to make booking process easily. It is also can increase the quality of the management and reduce the time constrains.